Association of CYP2C19 Polymorphism With Proton Pump Inhibitors Effectiveness and With Fractures in Real‐Life: Retrospective Cohort Study. Issue 5 (1st March 2022) - Gronich, Naomi; lavi, Idit; Lejbkowicz, Flavio; Pinchev, Mila; Rennert, Gad
Abstract : Symptom refractoriness of patients treated with proton pump inhibitors (PPIs) might be explained by polymorphism in CYP2C19. This is a retrospective cohort study in which we used the computerized database of Clalit Health Services to compose a cohort from cancer case‐control studies' participants that had been genotyped, and that have been dispensed PPI (January 1, 2002 to November 10, 2020). We retrieved demographic and clinical variables on date of PPI initiation (cohort entry), and studies' questionnaires‐reported consumption of foods/beverages known to increase peptic‐related symptoms. Primary outcome was an abdominal pain diagnosis; secondary outcome was a composite of abdominal pain, visit to a gastroenterology clinic, change to another PPI, PPI dose increase, or metoclopramide prescription, reflecting symptoms persistence/recurrence; in a 2‐year follow‐up. We also evaluated the association between genetic groups and hip/wrist/spine fractures, in a long‐term follow‐up. Of 3, 326 PPI initiators, there were 66 (2.0%), 739 (22.2%), 1394 (41.9%), 947 (28.5%), and 180 (5.4%) CYP2C19 poor, intermediate, normal, rapid, and ultra‐rapid metabolizers, respectively. Being a poor metabolizer was associated with lower risk for the primary outcome, hazard ratio (HR) = 0.50 (95% confidence interval (CI) 0.27–0.91), HR = 0.52 (95% CI 0.28–0.94); and for the secondary outcome, HR = 0.57 (95% CI 0.38–0.86), HR = 0.58 (95% CI 0.39–0.87), in univariate and multivariable cox regression analyses, respectively. In long‐term follow‐up with 20, 142 person‐years of follow‐up: 7.6% (5 cases) within the poor metabolizers group, and 11.6%, 12.9%, 12.8%, and 11.1% in the normal, intermediate, rapid, and ultra‐rapid metabolizers groups, respectively, had a new fracture (nonsignificant). We conclude that CYP2C19 poor metabolizer status is associated with higher effectiveness of PPIs, and is not associated with higher risk for fractures.